Breakthrough perspectives in network and data communications security, design, and applications - Bose, Indranil, 1968- (Advances in business data communications and networking., 2009)
"This book addresses key issues and offers expert viewpoints into the field of network and data communications, presenting research articles that address the most salient issues in network and data communications"--Provided by publisher.